Assessment of 2,2-diphenyl-1-picrilhidrazilo (DPPH) technique to determine antioxidant capacity - Guija-Poma, Emilio (2015)
We assessed the technique using free radical 2,2-diphenyl-1-picrilhidrazil (DPPH) used to determine the antioxidant capacity of foods and synthetic compounds; for that purpose this free radical has been used in concentrations between 0.037 and 0.2 mM, likewise, to perform this evaluation the catechin and epicatechin standards have been used in a concentration range of 6.67 x 10(-3) and 2.2 x 10(-2) mM. CI(50) values for both standards were dependent on the concentration of DPPH, having observed that the above value increases with increasing concentration of DPPH, for which reason it is suggested that all research use a single concentration of DPPH in the reaction medium.